DESIGN AND DEVELOPMENT OF ETHERNET CONTROL SYSTEM FOR EMBEDDED WEB SERVERUSING ARM PROCESSOR (International Journal of Engineering and Computer Science, 2014)
We describe the application of civil infrastructure for Monitoring and controlling long term degradation & bridge safety is the major concern to the government and the people. Although there are so much safety majors taken to ensure the protection of bridge, still there is no effective system which can monitor and control the status of the highway bridges from a centralized location. Aim of this proposed project is to develop the device that monitor the vibrations on the bridges, control the vehicles traffics on bridge by the traffic signal and carry the appropriate weight of vehicle on bridge. The values of these parameters are updated on the main PC server with the regular span of interval. The administrator helps to monitor the condition from any location in a web page. So it provides the idea related to maximum weight carriage capacity of the bridge & safety of the bridge. So any emergency situation like natural calamities such as earthquake, hurricanes, tornadoes, fire etc. occurs, the decision can be taken immediately after verifying the live data. This project has ARM processor based embedded system connected to Ethernet module which is connected to router. Personal IP address enters on HTML web page & this address is called from the host which is connected to the router.